CHARACTERISTICS OF THE RELATIONSHIP IN THE «MOTHER-CHILD» DYAD AND THE «MOTHER IMAGE» DYNAMICS IN THE PSYCHOANALYTIC PEDAGOGY OF DONALD WINNICOTT - Vertel, A. (Видавництво НДУ ім. М. Гоголя, 2023)
The article explains the concept of the British psychoanalyst, pediatrician and teacher Donald Winnicott regarding the special functions of the mother in early relations with the baby. Together with Anna Freud and Melanie Klein, he is considered to be the most influential representative of the European psychoanalytic pedagogy. A conceptual model of the earliest emotional development of a child is presented. It is shown that in the early stages after birth, the baby cannot be considered as an independent subject, but only in the «mother-child» dyad. In this regard, D. Winnicott introduces the concepts of «ideal» mother, «bad» mother, and «good enough» mother, which are very important for pedagogy. In the first months after the birth of a child, a «good enough» mother is in a state of «primary maternal anxiety» – this is a state of excessive, hyperbolized sensitivity, which creates conditions for the comprehensive disclosure of the child’s developmental tendencies and stimulates the first emotional impulses. It has been proved that a «good enough» mother should not only protect, satisfy basic (vital) needs, show care and love, but also allow the child to feel the effects of frustrations (special emotional states when the child, facing any obstacles, cannot achieve their goals and satisfy desires or needs), which are a prerequisite for normal child development. Only by facing frustrations does the child learn the reality of the outside world. It is shown that the mother not only creates the physical body of the child, bearing it in the womb, but also fundamentally influences the development of the «Ego»/«Self» of her newborn child. The process of personalization takes place thanks to maternal care, special support – «holding». Unlike the «good enough» mother, the «ideal» and «bad» mother form a false «Ego»/«Self» structure in the child. A «bad» mother does not establish a holding, thus forcing the child to prematurely adapt to a reality for which the child is not yet ready – he needs support. The «ideal» mother also contributes to the creation of a false «Ego»/«Self», she establishes a holding, but then does not let the child go, this forms infantilism in the child. Using D. Winnicott’s psychoanalytical concept, we offer psychological and pedagogical recommendations that will help to establish a relationship with the child. The recommendations will be useful not only for young parents and teachers, but also to pediatricians.
Keywords: psychoanalytic pedagogy; bad mother; upbringing; primary maternal concern; holding, transitional experience; true «Ego»/«Self»; false «Ego»/«Self»; good enough mother; ideal mother